10 - Interrogating the Cost of Digital Technology and Trust in Elections in Africa: The Nigerian Perspective - Okwueze, Felicia Osondu (Africa Development, 2022)
The adoption of technology in electoral democracy in Africa has been on the increase. The introduction of technology has its positive consideration but it also comes with cost and trust implications, which is a paradox. This study is a descriptive work which made use of both qualitative and quantitative analysis. Electionadministrationtheorywasadopted.Toimproveontheuseofdigital technologies, Africans should be mindful of the failure of digital checks and balances that often render an electoral process even more vulnerable to rigging than it was before. In designing new systems for election management, this article argues that Africans should look inward and integrate the new technologies into relevant environmental and cultural settings in order to reduce the cost while improving on the trust of electorates.